Integrin-linked kinase is dispensable for multiple myeloma cell survival - Steinbrunn, Torsten; Andrulis, Mindaugas (Leukemia research, 2012)
We investigated the utility of integrin-linked kinase (ILK) as a target for therapeutic intervention in multiple myeloma (MM). ILK (over-)expression was assessed in primary samples and MM cell lines, and the molecular and physiological consequences of siRNA-mediated ILK ablation were compared to treatment with the small molecule inhibitor QLT0267. Whereas ILK expression was ubiquitous, overexpression was only rarely observed in patient biopsies. ILK knockdown had no effect on the viability or survival pathway activity pattern of MM cells. Conversely, QLT0267 induced cell death in MM cell lines and most primary tumor samples via the intrinsic apoptotic pathway. Although this effect was largely tumor cell-specific it is unlikely to have been mediated via ILK. We conclude that ILK does not play a prominent role in the promotion or sustenance of established MM.